Clinical and electrocardiographic differences between apical and midventricular stress cardiomyopathy. (14th October 2021) - Esteban-Lucia, L; Martinez-Milla, J; Franco-Pelaez, J A; Lopez-Castillo, M; Martin-Reyes, R; Palfy, J; Romero-Daza, A; Pinero Lozano, A; Avila Barahona, P; Kallmeyer Mayor, A M; Gonzalez Lorenzo, O; Tunon, J
Abstract: Background: Stress cardiomyopathy (SCM) is a transient ventricular dysfunction frequently precipitated by acute emotional or physical stress. According to ventricular contractile pattern there are four SCM variants, being apical (80%) and midventricular (15%) the most frequents. Our aim is to describe the differences between these two SCM variants. Methods: We performed an observational study of patients who were diagnosed with SCM in our centre from February 2010 to January 2020. We registered demographic information, medical history, clinical, echocardiographic and analytical data of our patients and we performed a digital analysis of the 12-lead electrocardiogram (ECG) recorded in the first 48 hours after the onset of symptoms. Patients were divided into two groups, those with apical LV ballooning and patients with midventricular SCM. Results: We included 86 patients; baseline characteristics of the population are described in the table. The median age was 77 (IQR: 67.7–82.9), and 91.9% were female. Fifty-six patients (65.1%) had apical variant whereas thirty patients (34.9%) showed midventricular one. The most frequent antecedent trigger was an emotional stressor (36.3%) follow by physical stressor (identified in 23.8%). Chest pain was the most frequent clinical presentation (54.7%). Median LVEF was 35% (IQR 30.0–45.0) and mean basal septal thickness was 9.50 (IQR 9.0–11.0). Median peak of troponin level was 1.71 (IQR 0.6–3.4). Comparing apical and midventricular variants of SCM median age was 80.2 (IQR 68.9–84.5) in apical group and 71.6 (IQR 59.64–78.0) in midventricular variant (P=0.001). There were no other differences in the medical history, clinical, echocardiographic and analytical data between both groups (table). After comparative analysis of ECG we found differences in negatives T wave location and QT duration. Apical variant present more negative-T waves in leads II, III, AVF, V4, V5, V6, while in midventricular variant they are more present in AVR and AVL (figure 1). Mean QT duration was 508.0ms (IQR 470.0–552.0) in apical variant and 470.5ms (IQR 423.7–524.2) in midventricular group (p=0.026). There were no differences in Q waves between both groups. Conclusions: In our group of patients, apical and midventricular stress cardiomyopathy variants exhibit clinical and electrocardiographic differences. Patient with apical stress cardiomyopathy are older. They present more negative T waves in inferior and precordial leads, and longer QT interval. These results suggest that the pathophysiology of both entities could be different. FUNDunding Acknowledgement: Type of funding sources: None.